Labor in the Human Dimension: Losses and Acquisitions: X Meeting of the Interdisciplinary Scientific Discussion Club - O. A. Moskvitina (Научный диалог, 2017)
The announcement of the scientific event is presented. April 19, 2017 the Psychological Institute of the Russian Academy of Education organizes the X meeting of the interdisciplinary scientific discussion club “Labor in the Human Dimension: Loss and Acquisition”.